Gastroschisis. Prenatal sonographic markers and perinatal prognosis - Huerta Sáenz, Igor Hermann (2014)
Objectives: To determine extrabadominal intestinal loop dilation  and wall thickness as predictors of adverse perinatal outcomes in fetuses with gastroschisis. Design: Retrospective, observational, analytical correlation study. Setting: Fetal Surveillance Unit, Edgardo Rebagliati Martins National Hospital, EsSalud, Lima, Peru. Participants: Pregnant women with prenatal diagnosis of fetal gastroschisis. Interventions: We determined all patients with gastroschisis diagnosis from January 2008 through December 2010. Presence or absence of bowel dilatation and edema and postnatal intestinal outcome up to 6 months from birth were registered and compared with perinatal morbidity and mortality of babies without those alterations. Main outcome measures: Bowel dilation and wall edema by ultrasound. Results: According to the Registry of Fetal Surveillance Unit 19 cases of gastroschisis were found. One case was excluded because of other abnormalities present. Mean maternal age was 26.3 years and mean gestational age of pregnancy termination by cesarean section was 36.6 weeks. Eleven cases had birth weights less than percentile 10. In eight cases (44.4%) prenatal sonographic examination revealed dilated bowel loop over 20 mm diameter. No fetus died in utero. There were nine cases with intestinal complications, five with intestinal obstruction and four with intestinal perforation. Bowel obstruction occurred in 80% of cases with intestinal edema during prenatal sonographic evaluation. The positive predictive value of >20 mm dilation of intestinal loops was 0.75 for predicting intestinal complications. Four cases required re-operation. Ability to predict por postoperative evolution according to intestinal wall thickness had a sensitivity of 0.75. Stay in neonatal intensive care unit in groups with and without extra-abdominal dilatation was respectively 51.6 and 34.8 days, with significant difference. Conclusions: Ultrasonographic detection of extrabadominal intestinal loop dilatation at least three weeks before birth was predictor of intestinal complications in the postnatal period as well as neonatal ICU stay. Also wall edema correlated with surgical reinterventions of fetuses.